Caracterização termohigrométrica e de conforto térmico em Porto Velho no período de transição seco-chuvoso - Querino, Juliane Kayse Albuquerque da Silva (2017)
The Porto Velho municipality is in a constant development since your foundation until nowadays and this expansion modify the natural landscape, and consequently the microclimate. The main aim of this study was to study the pattern of the air temperature and humidity Porto Velho – RO throughout pre-determined points in the urban configuration by a mobile transect methodology. The period of measurement was between September and December of 2015 at 8h, 14h and 20h local time. The sensor was attached outside of a vehicle protected in the meteorological shelter. The entire route had 15 points of measurements. It was calculated comfort and discomfort index and also was applied ANOVA statistical analyses to testify the differences between the month and hour. To compare the averaged values was used Scott-Knott test with 5% of significance. The air temperature and humidity have shown differences between the points by mobile transect. It was observed that according to the landscape the air temperature increase next to the downtown and it was lower close to the areas with more vegetation. The air humidity values have showed that the vegetation had influenced in its pattern increasing the values in the points where vegetation are present. Due the urban influence, the values of temperature in the downtown have shown a 3C difference among its points and surrounding points even at night time. The comfort and discomfort index was classified like “comfort degrees varying” and “stress by the heat”.